Genomic Profiles of Neuroblastoma Associated With Opsoclonus Myoclonus Syndrome. Issue 2 (March 2018) - Hero, Barbara; Clement, Nathalie; Øra, Ingrid; Pierron, Gaelle; Lapouble, Eve; Theissen, Jessica; Pasqualini, Claudia; Valteau-Couanet, Dominique; Plantaz, Dominique; Michon, Jean; Delattre, Olivier; Tardieu, Marc; et al.
Abstract : Opsoclonus myoclonus syndrome (OMS), often called "dancing eyed syndrome, " is a rare neurological condition associated with neuroblastoma in the majority of all childhood cases. Genomic copy number profiles have shown to be of prognostic significance for neuroblastoma patients. The aim of this retrospective multicenter study was to analyze the genomic copy number profiles of tumors from children with neuroblastoma presenting with OMS at diagnosis. In 44 cases of neuroblastoma associated with OMS, overall genomic profiling by either array-comparative genomic hybridization or single nucleotide polymorphism array proved successful in 91% of the cases, distinguishing tumors harboring segmental chromosome alterations from those with numerical chromosome alterations only. A total of 23/44 (52%) tumors showed an segmental chromosome alterations genomic profile, 16/44 (36%) an numerical chromosome alterations genomic profile, and 1 case displayed an atypical profile (12q amplicon). No recurrently small interstitial copy number alterations were identified. With no tumor relapse nor disease-related deaths, the overall genomic profile was not of prognostic impact with regard to the oncological outcome in this series of patients. Thus, the observation of an excellent oncological outcome, even for those with an unfavorable genomic profile of neuroblastoma, supports the hypothesis that an immune response might be involved in tumor control in these patients with OMS.